Влияние марксистских идей на современную социально-политическую мысль - Шлома, А. К. (ХНУРЕ, 2020)
The article considers the influence of Marxist economic, philosophical and political ideas on the development of socio-political thought of the present. A thesis is put forward on the relevance of Marxist ideas for modern political science, philosophy and other humanities. Attention is focused on the fact that the central place in the work of K. Marx belongs to a critical analysis of capitalist society, its development prospects, and materialistic understanding of history.
Keywords: философия; влияние марксистских идей